Design and implementation of adaptive inverse control algorithm for a micro‐hand control system. Issue 1 (30th January 2014) - Wang, Wan‐Cheng; Liu, Tian‐Hua; Syaifudin, Yuddy; Wang, Tsan‐Kai
Abstract : The Letter proposes an online tuned adaptive inverse position control algorithm for a micro‐hand. First, the configuration of the micro‐hand is discussed. Next, a kinematic analysis of the micro‐hand is investigated and then the relationship between the rotor position of micro‐permanent magnet synchronous motor and the tip of the micro‐finger is derived. After that, an online tuned adaptive inverse control algorithm, which includes an adaptive inverse model and an adaptive inverse control, is designed. The online tuned adaptive inverse control algorithm has better performance than the proportional–integral control algorithm does. In addition, to avoid damaging the object during the grasping process, an online force control algorithm is proposed here as well. An embedded micro‐computer, cRIO‐9024, is used to realise the whole position control algorithm and the force control algorithm by using software. As a result, the hardware circuit is very simple. Experimental results show that the proposed system can provide fast transient responses, good load disturbance responses, good tracking responses and satisfactory grasping responses.